Effect of magnesium on free amino acid and polyamine content in wheat seedling exposed to cadmium stress - Leskó, Kornélia; Stefanovits-Bányai, Éva; Simon-Sarkadi, Lívia (Acta Biologica Szegediensis, 2002)
The effect of cadmium and combined cadmium and magnesium was examined on wheat seedlings (Triticum aestivum L. cv. Alföld-90). The one-week-old hydroponicallygrown wheat seedlings were exposed to Cd2+ (10-7 M, 10-3 M) and Cd2+ (10-7 M, 10-3 M) + 1 % MgCl2 stresses. Free amino acid content was determined by ion-exchange liquid chromatography. Polyamine content was identified by OPLC (overpressured layer chromatography). The results showed significant differences between the two organs of the plant (root and shoot). The cadmium stress caused typical accumulation of proline in both shoots and roots. Whereas in the samples treated with combined cadmium and magnesium proline content decreased. The magnesium treatment seemed to reduce the negative effects of cadmium in wheat seedlings. With respect to the total free polyamine content, considerable decrease in shoots and increase in roots were found under stress conditions. The major components were agmatine, putrescine and spermidine. Organ-specific changes were found in the case of agmatine.